ConBr lectin modulates MAPKs and Akt pathways and triggers autophagic glioma cell death by a mechanism dependent upon caspase-8 activation - Wolin, Ingrid A. V. (2021)
Glioblastoma multiforme is the most aggressive type of glioma, with limited treatment and poor prognosis. Despite some advances over the last decade, validation of novel and selective antiglioma agents remains a challenge in clinical pharmacology. Prior studies have shown that leguminous lectins may exert various biological effects, including antitumor properties. Accordingly, this study aimed to evaluate the mechanisms underlying the antiglioma activity of ConBr, a lectin extracted from the Canavalia brasiliensis seeds. ConBr at lower concentrations inhibited C6 glioma cell migration while higher levels promoted cell death dependent upon carbohydrate recognition domain (CRD) structure. ConBr increased p38MAPK and JNK and decreased ERK1/2 and Akt phosphorylation. Moreover, ConBr inhibited mTORC1 phosphorylation associated with accumulation of autophagic markers, such as acidic vacuoles and LC3 cleavage. Inhibition of early steps of autophagy with 3-methyl-adenine (3-MA) partially protected whereas the later autophagy inhibitor Chloroquine (CQ) had no protective effect upon ConBr cytotoxicity. ConBr also augmented caspase-3 activation without affecting mitochondrial function. Noteworthy, the caspase-8 inhibitor IETF-fmk attenuated ConBr induced autophagy and C6 glioma cell death. Finally, ConBr did not show cytotoxicity against primary astrocytes, suggesting a selective antiglioma activity. In summary, our results indicate that ConBr requires functional CRD lectin domain to exert antiglioma activity, and its cytotoxicity is associated with MAPKs and Akt pathways modulation and autophagy- and caspase-8- dependent cell death.